(untitled) (Fiep Bulletin - online, 2016)
The main objective of this paper is to discuss playing, in the childhood education, as a crucial element to the development of the educational practices. This paper is a bibliographical study with a reflective analysis, which has as questioning: the play is relevant to early childhood education? The act of playing with the children has been discussed as a component and axis of the planning in the pedagogical work with children among 0 and 5 years,combined with the aspects of care and education, which leads teachers to rethink their articulation in activities proposition. The child at this stage of early childhood education is connected to the world of play, and learns through that, thus when working curricular contents organizing ludic situations and that propose challenges that mobilize cognition, this can result in a more effective way learning.The play is an integral part of childhood education, without this there is no child’s identification with the educational environment.